PROGRESSION OF AORTIC AND VALVULAR HEART DISEASES IN PATIENTS WITH ANKYLOSING SPONDYLITIS - A. A. Godzenko; Yu. O. Korsakova; O. A. Rumyantseva; A. G. Bochkova; V. V. Badokin; Sh. F. Erdes (Научно-практическая ревматология, 2017)
Involvement of the aorta and heart valves in ankylosing spondylitis (AS) is a manifestation of the systemic inflammatory process. Data on the frequency, clinical significance, and evolution of these manifestations are controversial.Objective: to estimate the time course of echocardiographic (EchoCG) changes in the aorta and heart valves from the results of a prospective follow-up study of patients with AS.Subjects and methods. In 2008 to 2015, the V.A. Nasonova Research Institute of Rheumatology followed up 45 patients (35 men and 10 women) with documented AS that was consistent with the modified New York criteria and the original EchoCG changes in the aorta and heart valves. All the patients underwent transthoracic echocardiography at baseline and after 1–5 years. At baseline, there was aortic root dilatation (>37 mm) in 15 patients, thickening of the aortic walls and aortic valve (AV) cusps in 21 and 32 patients, respectively, as well as thickening of the mitral valve (MV) cusps in 15, and valve prostheses in 5 patients (2 had AV and MV prostheses). Aortic regurgitation (AR) was recorded in 19 patients (grades 1–2 AR in 15 patients and grades 3–4 in 4 patients); grades 1–2 mitral regurgitation (MR) was seen in 20 patients. Ten patients had subaortic pectinate thickening (SPT) in the aortomitral junction area. Of the 45 patients, 16 took biological agents (BA); 29 received traditional therapy, including 14 patients who used nonsteroidal anti-inflammatory drugs, 11 and 4 patients had sulfasalazine and methotrexate, respectively.Results and discussion.Repeated examinations revealed negative changes in 27 (60%) of the 45 patients. Progressive aortic dilatation (1 to 6 mm) was found in 12 (80%) of the 15 patients; dilatation appeared during follow-up in 2 patients. Fourteen patients were noted to have negative valve changes: the emergence of cusp thickening in the valves (that in AV and MV in 9 and 4 patients, respectively; both in 1 patient). Four patients underwent valve replacement: 3 and 1 patients underwent AV and MV replacements, respectively. Ten of the 19 patients were observed to have AR progression by 2 grades in 2 (10.5%) patients and by one grade in 8 (42.0%) patients. MR progression by one grade was noted in 6 (30.0%) of the 20 people. A negative correlation was found between BA therapy and aortic dilation progression (r = -0.329; p = 0.03). SPT appeared in 3 patients. Of the 10 patients who had a baseline SPT, its reduction (8 to 3.5 mm) was seen in one patient; complete regression was identified in two patients; all received BAs. Thus, pathological changes in the aorta and heart valves in AS are progressive in most patients. SPT may regress, which reflects apparently a reduction in the severity of active inflammation of the aortic root. Active anti-inflammatory treatment may play a protective role in the progression of aortic dilatation.